The Effect of Credit on the Export Performance of Colombian Exporters - Danielken Molina; Mónica Roa (Inter-American Development Bank (IDB), 2014)
In this paper we use Colombian manufacturing data on exports and external financing for the period 1998 - 2006 to estimate the credit elasticity of exports. We use bank-firm linked data to construct a supply side instrument for a manufacturer's demand of credit, which we use to address the reverse causality between a manufacturer's export revenue and its demand for credit. We find that access to credit produces a significant increase on a manufacturer's export revenue explained by the positive effect of credit on an exporter's market reach - number of destinations -. Across manufacturers the effect of credit on a manufacturer's export revenue varies by size. While medium sized manufacturers use credit to increase their market reach, market penetration and product mix, large manufacturers only use credit to increase their market reach. Small manufacturers do not seem to benefit from bank credit.
hdl:11319/6516
Keywords: F14; G21; 330; Trade; Export Margins; Bank Financing